Labour Standards in Global Value Chains: Disentangling Workers’ Voice, Vicarious Voice, Power Relations, and Regulation - Josserand, Emmanuel; Kaine, Sarah (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
Theoretical developments and case studies have started to explore the complexity and intricacies of new forms of labour regulation in Global Value Chains (GVCs). This paper builds on these to integrate what we know into a coherent framework that can guide practice and future research. We bring together existing knowledge on new forms of labour standards regulation—such as Private Social Standards (PSSs) and International Framework Agreements (IFAs)—into a framework that integrates and disentangles the contextual determinants, processes, regulatory mechanisms, and outcomes of such regulation in GVCs. Of special significance is the distinction between regulatory processes—vicarious voice, workers’ voice, coordinated international campaigns—, and regulatory mechanisms—IFAs and PSSs. Extant literature tends to deal with existing forms of regulation without much clarity on their respective roles. Our framework identifies two pathways from regulatory processes to regulatory mechanisms: the labour power and the customer power pathways. Our framework also establishes clear connections between concepts, underlining links of causality and moderating effects.We explore the impact of value chain structure, and specifically, the connections between workers’ and vicarious voice, on regulatory outcomes. With regard to the structure of supply chains, we examine the coupling of operations and the sensitivity of value chain participants to reputational risk and drive within value chains. We add the significant dimension of ‘internal drive’ to existing understandings of drive to capture the possible internal discrepancies leading managers in multinational companies (MNCs) to apply mixed incentives to their suppliers to comply with labour standards. Additionally, we introduce the concept of ‘vicarious voice’, which we define as a situation where workers’ voice is substituted by that of actors who, unlike local unions or activist unionism, do not have a close representative link with workers. Vicarious voice may be composed of ethical consumerism, social advocacy, and international union federations.